The sensitivity of isometric versus ballistic measures of rapid force production following ballistic speed-strength training: A systematic review and meta-analysis - James, L. P.; Talpey, S. W.; Stutter, L. R.; Häkkinen, K.; Huynh, M. (International Journal of Sports Physiology and Performance, 2025)
Background: Accurate assessment of rapid force production is essential for monitoring adaptations to ballistic speed-strength training, a modality central to athletic performance enhancement. Both dynamic (eg, countermovement-jump height or drop-jump reactive strength index) and isometric (eg, rate of force development) tests are commonly used, yet their relative sensitivity to training-induced change remains unclear. Purpose: To systematically review and analyze the literature to establish whether measures of dynamic or isometric rapid force production were more sensitive to ballistic speed-strength training. In addition, subgroup analysis was performed to evaluate whether the type and temporal aspects of isometric test and associated measures had an impact on the effect. Methods: A systematic search of databases for eligible articles was conducted up to February 2025. A multivariate random-effects meta-analysis with adjustment for within-study dependencies was employed. Results: Five studies yielded 15 isometric-dynamic change comparisons, and a total of 82 participants were included in the final analysis. The pooled analysis indicated no significant difference between isometric and dynamic measures following ballistic speed-strength training. Prediction intervals were wide, indicating substantial variability in outcomes across settings. Subgroup analyses similarly revealed no consistent moderating effect. Conclusions: The magnitude of change in isometric versus dynamic measures of rapid force production can be expected to vary considerably in future practical or experimental settings following ballistic speed-strength training. Practitioners should closely monitor individual responses and avoid assuming uniform training effects for these 2 forms of testing across all athletes.